Olympic Games in COVID-19 times: lessons learned with special focus on the upcoming FIFA World Cup Qatar 2022 - Dergaa, I.; Ben Saad, H.; Souissi, A.; Musa, S.; Abdulmalik, M. A.; Chamari, K. (British Journal of Sports Medicine, 2022)
The COVID-19 pandemic has impacted the global international sports calendar, causing the first-ever postponement of the 2020 Tokyo Summer Olympic Games (OG) and Paralympic Games (PG) until 2021.Several scientists and sports organisations were strongly opposed to the organisation of these OG and PG. Variable vaccination rates, waning immunity and the emergence of more transmissible and potentially lethal COVID-19 strains have created additional challenges to hosting large-scale international sporting events. Contrary to the 2020 Tokyo Games, which were held without fans, another mega event, the FIFA World Cup 2022, will be held in Qatar (21 November-18 December) with over 1.7 million expected visitors (fans, staff, players and media).